Upregulation of Extracellular Vesicles-Encapsulated miR-132 Released From Mesenchymal Stem Cells Attenuates Ischemic Neuronal Injury by Inhibiting Smad2/c-jun Pathway via Acvr2b Suppression - Feng, Bin; Meng, Lei; Luan, Liming; Fang, Zhihao; Zhao, Peng; Zhao, Guangyu (Frontiers in Cell and Developmental Biology, 2021)
Ischemic cerebrovascular disease is a significant and common public health issue worldwide. The emerging roles of mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) in ischemic neuronal injury continue to be investigated. The current study aimed to investigate the role of EV-derived miR-132 from MSCs in ischemic neuronal injury. EVs were initially isolated from bone MSCs (BMSCs) and subsequently evaluated. A middle cerebral artery occlusion (MCAO) mouse model was constructed with the neurological function evaluated through a series of neurological scores, a pole test, and a foot fault test. Histopathological changes, neuron viability, and apoptosis, as well as cerebral infarction, were detected by hematoxylin and eosin (HE) staining and 2,3,5-triphenyltetrazolium hydrochloride (TTC) staining. The targeting relationship between microRNA (miR)-132 and Activin receptor type IIB (Acvr2b) was further confirmed based on dual-luciferase reporter gene assay results. Loss- and gain-of-function assays were conducted to elucidate the role of miR-132, EV-derived miR-132, Acvr2b, and Smad2 in oxygen-glucose deprivation (OGD)-treated neurons, and in mice models. Neuronal cell viability and apoptosis were evaluated via Cell Counting kit-8 (CCK-8) and flow cytometry. Our results indicated that Acvr2b was highly expressed, while miR-132 was poorly expressed in the MCAO mice and OGD-treated neurons. Acvr2b silencing or upregulation of miR-132 led to an elevation in neuronal activity, decreased neuronal apoptosis, reduced expression of Bax, and cleaved-caspase 3, as well as increased Bcl-2 expression. Acvr2b expression was targeted and inhibited by miR-132. EV-derived Acvr2b promoted activation of phosphorylated-Smad2 (p-Smad2)/c-jun signaling pathway, ultimately inducing neuronal injury. Our study provides evidence demonstrating that the overexpression of c-jun inhibits the protective role of MSCs-derived EV-miR-132 in neuronal injury. Upregulation of EV-derived miR-132 released from MSCs attenuates ischemic neuronal injury by inhibiting Smad2/c-jun pathways via the suppression of Acvr2b.